Effectiveness of organic wastes and forages to increase soil fertility status and crop yield in dry lands - N M L Ernawati; I K Ngawit; N Farida (Brawijaya University, 2014)
The main purpose of this study was to elucidate the effects of application of organic wastes and rotation of cropping system on soil fertility status and yields of dry field rice, maize, soybean, groundnut and mungbean in order to overcome soil degradation problems in dry land areas. Six cropping rotation systems (dry field rice-soybean-fallow, dry field rice-groundnut-fallow, dry field rice-mungbean-fallow, maize-soybean-fallow, maize-groundnut-fallow, and maize-mungbean-fallow), and six organic fertilizer rates (0, 5, 10, 15, 20 t/ha, and 25 t/ha) were arranged in a randomized block design with two replicates. The results showed that maize-groundnut-fallow and dry filed rice-groundnut-fallow cropping systems with application of 25 t/ha organic fertilizer were able to increase soil fertility status. At the two cropping systems, status of N-total, P-total, K-total, C-total, CEC, and soil pH were better than other treatments. Soil physical fertility status on maize-groundnut-fallow and dry filed rice-groundnut-fallow cropping systems with application of 25 t/ha organic fertilizer was better than other treatments. Implication of improvement of soil physic characteristic because of this treatment was capable of raising irrigation efficiency about 0.98. Soil biological fertility at the same treatments was also better than other treatments. The average of soil worms was 2.44 per m2 soil. The amount of bacteria was 3.284 x 106 per gram soil. The amount of colony was 545.78 and the average of colony forming holozone was 19.66. Application of 20-25 t/ha organic fertilizer yielded higher crop yields than application of 0, 5, 10, an 15 t/ha organic fertilizer. Maize-groundnut-fallow cropping system and 25 t/ha application of organic fertilizer resulted in the highest propriety index, with value BC-ratio 2.54, BEPproduction 61760, and BEPvalue 982.